1988
DOI: 10.1016/s0190-9622(88)70079-1
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur revisited

Abstract: Sulfur is a time-honored therapeutic agent useful in a variety of dermatologic disorders. Its keratolytic action is due to formation of hydrogen sulfide through a reaction that depends upon direct interaction between sulfur particles and keratinocytes. The smaller the particle size, the greater the degree of such interaction and the greater the therapeutic efficacy. When applied topically, sulfur induces various histologic changes, including hyperkeratosis, acanthosis, and dilatation of dermal vasculature. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 16 publications
0
34
0
2
Order By: Relevance
“…Esto permite que se desprendan las escamas y, por consiguiente, los ácaros. Además, al disolver los surcos acarinos, el azufre actuaría con mayor facilidad sobre los ácaros (Lin et al, 1988). Asimismo, debe tomarse en consideración el efecto de aniquilamiento por oclusión y sofocación que ocasiona la vaselina a cortar el suministro de oxígeno a este tipo de ácaros (Astigmata), así como a otros tipos de ectoparásitos que poseen la cutícula muy fina (Jacobson y Abel, 2007).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Esto permite que se desprendan las escamas y, por consiguiente, los ácaros. Además, al disolver los surcos acarinos, el azufre actuaría con mayor facilidad sobre los ácaros (Lin et al, 1988). Asimismo, debe tomarse en consideración el efecto de aniquilamiento por oclusión y sofocación que ocasiona la vaselina a cortar el suministro de oxígeno a este tipo de ácaros (Astigmata), así como a otros tipos de ectoparásitos que poseen la cutícula muy fina (Jacobson y Abel, 2007).…”
Section: Resultados Y Discusiónunclassified
“…El conocimiento de la acción acaricida del azufre es milenario (Lin et al, 1988) y el azufre precipitado en petrolato es utilizado tradicionalmente para el tratamiento de la sarna knemidocóptica (Chauhan y Roy, 1996). Tiene la ventaja de su bajo costo y sus componentes son de amplia disponibilidad en los mercados farmacéuticos de los países en desarrollo.…”
Section: Introductionunclassified
“…It has recognized fungicidal, bactericidal and antipruritic properties, and therefore it is used for the therapy of mite infestations in animals. Sulfur was even proposed as an antidote for acute exposure to radioactive material (8). Indeed, it has been demonstrated that sulfurs favor wound healing, acts as a keratolytic agent and can induce various histological modifications in the skin (including hyperkeratosis, acanthosis, and dilation of dermal vessels).…”
Section: Sulfurs In Skin Therapymentioning
confidence: 99%
“…The technique is very simple: after a preliminary bath, the sulphur ointment is applied and thoroughly rubbed into the skin over the whole body for two or three consecutive nights. 16 Patients should apply the ointment personally, as it ensures that their hands will be well impregnated. Ointments are more useful than any other preparation.…”
Section: Sulphurmentioning
confidence: 99%